David Copperfield - Dickens, Charles, 1812-1870 (Delhi : Global Media, 2007)
A boy grows to maturity in the affairs of the world and of the heart, surrounded by some of the author's most memorable characters. However, will David find happiness with the faithful Agnes Wickfield, whom he has known since childhood? Threatened by Uriah Heep, her father's clerk, the security of her own future is in question
Title from container
System requirements: Window 95/98/ME/2000/NT/XP/Vista ; 16 MB RAM or greater ; CD-ROM drive 4x or greater Pentium PC or higher ; 16 bit sound card ; 50 MB available HD space ; 256 colour VGA monitor or greater ; Macromedia Flash Player ; Adobe Acrobat Reader
Keywords: Boys -- Fiction; England -- Fiction; Orphans -- Fiction; Young men -- Fiction; Stepfathers -- Fiction; Child labor -- Fiction